Analisa Vitamin C dan Evaluasi Sediaan Tablet Effervescent Campuran Ekstrak Etanol Biji Jambu Biji Merah dan Putih (Psidium guajava L.) - Hendri Faisal; Suprianto; Nur Aisyah Pitri; Sri Handayani; Dwi Setio Purnomo (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Effervescent tablets, CO2-producing tablets from the reaction of tablet constituents with their solvents. Red guava contains beta-carotene vitamin C is quite high, white guava is rich in vitamins, flavonoids, carotenoids, saponins, tannins, phenols, triterpenes, essential oils, fiber, and fatty acids. The study aimed at the comparison of vitamin C extract of red and white guava seeds (Psidium guavala. L). Powder evaluation includes flow time, angle of repose, compactibility. The evaluation of tablets included organoleptic, soluble time, weight uniformity, hardness, friability, pH, vitamin C content using UV spectrophotometry method. The results showed that the flow time test was 11.31-16 gram/second, the angle of repose was 33.02-34.92%; compactibility 7.59-16.9%; effervescent tablet preparation is round in shape, brown aroma, dark brown-brown color, slightly sweet taste, dissolving time 33.79- 89.53 seconds; hardness 4-5,4 kg; friability 0.04-0.9%; pH is close to neutral at pH 5.83-6.39; vitamin C content of red and white guava seeds were 37.86 mg/g and 42.32 mg/g, respectively. Red and white guava seed extract can be formulated into effervescent tablets and has vitamin C 0.19 – 0.28 mg/g